RASIONALIITAS PENDIDIKAN FORMAL ANAK SUKU BONAI - Yance "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is entitled “Formal Education of Bonai Tribe Children: An Analysis of Rational Action”. Researchers are very interested in bringing up this theme because they want to know how people view formal education. The analysis in this research is descriptive qualitative analysis. Which is related to the rationality of the Bonai Tribe in formal education. The formulation of the problem in this study are (1) What is the meaning of formal education for the Bonai Tribe?.(2) How is the rationality of the Bonai Tribe in taking formal education?.Data collection techniques in this research is by interview. The community informants who became research informants were determined by random sampling. The results of this study show the enthusiasm of the children of the Bonai Tribe in taking formal education, the support given by the parents of the Bonai Tribe children is also very large to support the formal education of the children of the Bonai Tribe.Keywords: Educational rationality, Meaning of Education, Bonai Tribe